Pendayagunaan Zakat Profesi dalam Pemberdayaan Ekonomi Mustahik Berdasarkan Prinsip Maqashid Syariah di BAZNAS - Asep, Asep; Amelia, Mike (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2024)
Empowerment is a change in circumstances through the help of other parties and is inclusive by involving the objects of the program targets. Economic empowerment by using zakat funds must always be in the corridor of fulfilling the pillars of zakat. Zakat as a worship that has two dimensions, namely in addition to being a form of obedience to Allah SWT, it is also a concern or obligation towards fellow human beings. The purpose of this study is to analyze the utilization of professional zakat in empowering the economy of mustahik based on the maqasid sharia principle at Baznas Bekasi Regency, descriptive analysis method by identifying from several sources including books, journals, websites, the Qur'an and Hadith, and the results of interviews with Baznas, it can be described that the implementation of zakat funds obtained by Baznas Bekasi Regency which comes from the State Civil Apparatus and the private sector in the Bekasi Regency area, is used for empowering the economy of mustahik through the Bekasi Pintar, Bekasi Taqwa, Bekasi Mandiri, Bekasi Sehat and Bekasi Peduli programs, the five leading programs are based on the maqasid sharia principle by considering the conditions of mustahiq.